The effect of the snowball strategy on the skill of solving mathematical problems and developing reflective thinking among second-year intermediate students - Dr.Riyadh Jumaah ail algailani (Journal of College of Education, 2025)
The research aims to identify the effect of the snowball strategy on the skill of solving mathematical problems and developing reflective thinking among second-year intermediate students in mathematics for the academic year (2023-2024), and for checking research objective, number of null hypotheses were formulated, and used the experimental method with two equal groups. The research sample included (61) students who were intentionally selected from Zozak Intermediate School for Boys, it was distributed randomly into two groups, one of which was an experimental group of (30) students who studied according to the Snowball strategy, and the other was a controlled group of (31) students who studied according to the normal method, The process of equivalence between the two research groups was also carried out in a number of variables. To achieve the research objectives, two tests were prepared: the first is a Testing the skill of solving a mathematical problem, in its final form, consisting of (12) items, and the second is a reflective thinking test, in its final form, consisting of (15) items. Their validity, stability, and psychometric properties were verified, after processing the data statistically using the t-test for two independent samples and two correlated samples, and using the statistical program (SPSS), the results showed that the experimental group was superior to the control group in the Testing the skill of solving a mathematical problem and the reflective thinking test. It also showed that there was a difference between the average scores The students of the experimental group in the reflective thinking test, pre- and post-test, in favor of the post-application.
Keywords: snowball strategy; mathematical problem-solving skill; reflective thinking